Sumber Hukum Keluarga Islam Di Indonesia: Antara Hukum Negara, Hukum Islam, Dan Hukum Adat - Syahroni, Akhmad; Sukti, Surya (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study examines the interaction between the three main sources of law in the context of Islamic family law in Indonesia, namely state law, Islamic law, and customary law. Using a philosophical approach, this paper evaluates the extent to which the interaction between these legal sources fulfills the principles of justice, legal certainty, and utility. The findings indicate that legal pluralism creates complex dynamics, particularly in cases of interfaith marriage, polygamy, and inheritance. The main challenge lies in the inconsistency between state law, Islamic law, and customary law, which often leads to legal uncertainty and injustice, especially for women. Recommendations include revising the Marriage Law and the Compilation of Islamic Law (KHI), harmonizing legal sources, and increasing legal awareness among the public. This paper is expected to contribute to the development of a more just and harmonious family law system in Indonesia.